Oil Price Shocks and the Macroeconomy: Chronicles of Theory and Empirics (2016)
Understanding energy-economy interactions has occupied the attention of academics and policymakers for several decades. The preponderance of empirical attempts in this sphere has focused on the impact of oil price shocks on the aggregate economy in both developed and developing economies. This expansive literature has undoubtedly produced diverse and often conflicting results. In this paper, we therefore provide a survey of this vast literature on the oil shocks-macroeconomy relationship. In particular, we carefully document a considerably elaborate account of both the theoretical propositions as well as empirical exercises in this literature especially over the last three decades on the relationship in question. The core idea behind the foregoing is the hope that this will help both academic researchers and policymakers in the quest for a better understanding of the oil price-macroeconomy nexus particularly in resource dependent settings.